(3fRgI GdCdHGH GdLGeYI dafhf GdBOGHs - (3YHO Gddg Hf YHO Gddg Hf SdGeg GdCOcGhj GdTGaYj GdeYQha HGdeDPfs
(3ChdgG (B:s
(3MeOkG def Rjf eMGad GdNdaGA HeMGSf GdCOHGA, hCfgV gege dGcJSGH GdeYGdj, aGcJSHhG ef MddgG OjHGLkG ePgHkG s
(3BNQgG (B:s
(3haj GdUMa YGbH, haj GdRHhQ aGQhb, hYfO Gddg JYGdi Wg, hYfO GdeDefjf eMeO, hocfjJg CHhGdbGSe s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B138 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs